2024
DOI: 10.3389/fimmu.2024.1296061
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-derived extracellular vesicles: endogenous roles, therapeutic potentials and their biomimetics for the treatment and prevention of sepsis

Clement Yaw Effah,
Xianfei Ding,
Emmanuel Kwateng Drokow
et al.

Abstract: Sepsis is one of the medical conditions with a high mortality rate and lacks specific treatment despite several years of extensive research. Bacterial extracellular vesicles (bEVs) are emerging as a focal target in the pathophysiology and treatment of sepsis. Extracellular vesicles (EVs) derived from pathogenic microorganisms carry pathogenic factors such as carbohydrates, proteins, lipids, nucleic acids, and virulence factors and are regarded as “long-range weapons” to trigger an inflammatory response. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 200 publications
0
1
0
Order By: Relevance
“…It has been shown that immune cells can recognize and interact with these exogenous EVs to alter their responses to stimuli [39]. Only one study showed that exogenous EVs promote immune tolerance (Table 9).…”
Section: Promotion Of Immune Tolerancementioning
confidence: 99%
“…It has been shown that immune cells can recognize and interact with these exogenous EVs to alter their responses to stimuli [39]. Only one study showed that exogenous EVs promote immune tolerance (Table 9).…”
Section: Promotion Of Immune Tolerancementioning
confidence: 99%